Predicting Global Cognitive Decline in the General Population Using the Disease State Index - Cremers, Lotte G. M.; Huizinga, Wyke; Niessen, Wiro J.; Krestin, Gabriel P.; Poot, Dirk H. J.; Ikram, M. Arfan; Lötjönen, Jyrki; Klein, Stefan; Vernooij, Meike W. (Frontiers in Aging Neuroscience, 2020)
Background: Identifying persons at risk for cognitive decline may aid in early detection of persons at risk of dementia and to select those that would benefit most from therapeutic or preventive measures for dementia. Objective: In this study we aimed to validate whether cognitive decline in the general population can be predicted with multivariate data using a previously proposed supervised classification method: Disease State Index (DSI). Methods: We included 2,542 participants, non-demented and without mild cognitive impairment at baseline, from the population-based Rotterdam Study (mean age 60.9±9.1years). Participants with significant global cognitive decline were defined as the 5% of participants with the largest cognitive decline per year. We trained DSI to predict occurrence of significant global cognitive decline using a large variety of baseline features. Prediction performance was assessed as area under the receiver operating characteristic curve (AUC), using 500 repetitions of 2-fold cross-validation experiments. Results: A mean AUC (95% confidence interval) for DSI prediction was 0.78 (0.77 - 0.79) using only age as input feature. When using all available features, a mean AUC of 0.77 (0.75 - 0.78) was obtained. Without age, and with age-corrected features and feature selection on MRI features, a mean AUC of 0.70 (0.63 - 0.76) was obtained, showing the potential of other features besides age. Conclusion: The best performance in the prediction of global cognitive decline in the general population by DSI was obtained using only age as input feature. Other features showed potential, but did not improve prediction. Future studies should evaluate whether the performance could be improved by new features, e.g., longitudinal features, and other prediction methods.